The Influence of Internal Communication and Work Climate on Personnel Collaboration in the Directorate of Civil Affairs, Royal Thai Air Force - Supprasert, Theerasak; Thongyot, Wimonthip; Phunsiaem, Phunthira; Kaewchur, Pornthep (ARU Research Journal Humanities and Social Sciences, 2026)
This study aimed 1) to examine the levels of internal communication, work climate, and personnel collaboration; and 2) to analyze the influence of internal communication and work climate on personnel collaboration in the Directorate of Civil Affairs, Royal Thai Air Force. A quantitative research approach was employed with a sample of 220 civil servants and government employees. Data were collected using a questionnaire and analyzed using descriptive statistics and multiple regression analysis. The findings revealed that internal communication, work climate, and personnel collaboration were generally rated at a high level. All dimensions of internal communication and work climate had positive and statistically significant influences on personnel collaboration. Among the internal communication factors, communication consistency, communication channels, and two-way communication exerted the strongest influences, whereas the most influential dimensions of work climate were coworker relationships and supervisory support. Organizational fairness also had a significant influence, although its relative contribution was lower than that of the other factors. A key finding of the study is that, in hierarchical and command-oriented organizations such as military institutions, the continuity and consistency of communication appear to play a more prominent role in promoting personnel collaboration than the clarity of information alone. This finding highlights the importance of organizational context in understanding the effects of internal communication and extends existing knowledge by demonstrating how communication practices operate within hierarchical organizational structures. The findings may therefore serve as a basis for developing internal communication policies and improving the work climate in ways that strengthen personnel collaboration in public-sector organizations and other organizations characterized by hierarchical administrative structures.